2022
DOI: 10.3390/nu15010160
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin E Supplementation in Postmenopausal Women—A Systematic Review

Abstract: Menopause is a physiological change in any woman. Nevertheless, its symptoms could be difficult to accept, and hormone therapy can be sometimes unattractive or contraindicated. Vitamin E components are phytoestrogens, so they are believed to be useful in some indications including menopause. This review aimed to assess the available evidence on the effectiveness of vitamin E in alleviating menopausal symptoms. The Pubmed/MEDLINE, Cochrane Library and Scopus databases were screened. All types of studies that as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…This has negative effects on sexuality and sexual function. Studies report that dyspareunia and postmenopausal vaginal health are taboo topics for a substantial number of patients ( 28 , 29 ). Both healthcare professionals and patients may find it difficult to approach the subject of sexual problems associated with menopause and vulvovaginal atrophy ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has negative effects on sexuality and sexual function. Studies report that dyspareunia and postmenopausal vaginal health are taboo topics for a substantial number of patients ( 28 , 29 ). Both healthcare professionals and patients may find it difficult to approach the subject of sexual problems associated with menopause and vulvovaginal atrophy ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Porterfield et al ( 27 ) summarized evidence for vaginal vitamin E efficacy in reducing patient-reported genitourinary symptoms in healthy postmenopausal patients compared with placebo or vaginal estrogen. A review by Feduniw et al ( 28 ) concluded that vitamin E might be an option for standard hormone therapy and may be an option to treat symptomatic patients with contraindications to estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a significant number of women currently exhibit reluctance to pursue HT, primarily attributed to apprehensions regarding associated risks [44]. Nonhormonal treatments, such as selective serotonin reuptake inhibitors (SSRIs) or serotoninnorepinephrine reuptake inhibitors (SNRIs), offer a promising approach to addressing menopausal symptoms in women [45]. Extensive research has confirmed the effectiveness of non-hormonal treatments in significantly diminishing the intensity and severity of HF, with reported decreases of up to 70-80% [46].…”
Section: Discussionmentioning
confidence: 99%
“…It has an important effect on the clinical manifestations of the climacteric, especially on postmenopausal vasomotor symptoms, vaginal, neurological and vascular changes. (28) Radnia N, Hosseini ST, et al; carried out a randomized clinical trial with a population of 64 postmenopausal women who presented genitourinary syndrome, they were divided into 2 teams (1 study and 1 control). The study group used vaginal creams combined with vitamins D and E, and the control group was treated with vaginal creams based on conjugated estrogens for a period of 12 weeks, regular visits were made where libido, vaginal symptoms (pruritus, dryness and dyspareunia) improved in both trials, it was concluded in this research that the use of vaginal creams of vitamins D and E have the same positive and beneficial effect as creams with conjugated estrogens.…”
Section: Phytoestrogensmentioning
confidence: 99%